EFFECT OF BACOSIDE A ON LIPID PEROXIDATION IN D-GALACTOSE INDUCED AGING MICE - Pawar, Sushama; Jadhav, Manmohini (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Bacoside A is a major bioactive constituent of Bacopa monnieri L having antioxidant property. The objective of this study was to evaluate the effect of Bacoside A, on lipid peroxidation in brain, heart and liver during induced aging. Methods: Male Swiss albino mice, Mus musculus was used for the present investigation. Four experimental groups were used as Group I-Normal adult, Group II-D-galactose induced, Group III-D-galactose induced plus Bacoside A treated and Group IV-Natural aging. The effect of Bacoside A was studied against lipid peroxidation during induced aging. The level of lipid peroxidation in the form of MDA formation was determined and measured in brain, heart and liver. Results: The statistical data obtained were analyzed using one way ANOVA, control vs other groups and results were expressed as meanÂ±SE. In Bacoside A treated group the lipid peroxidation level in heart, brain and liver was significantly decreased (p<0.001) compared to control group. A significant increase (p<0.0001) in the level of lipid peroxidation was observed in D-galactose induced mice. In natural aging group highly significant increase (p<0.0001) in initial lipid peroxidation, ascorbate dependent lipid peroxidation and spontaneous lipid peroxidation was observed. Conclusion: The observations revealed that, lipid peroxidation was reversed in Bacoside A treated group which may be due to antioxidant property of Bacoside A. Thus Bacoside A is able to ameliorate the stress induced changes in lipid peroxidation during aging. The findings also provide a theoretical basis for the development of novel therapeutic formulations, such as antioxidant supplementation to boost antioxidant defenses in the body.